ผลของซิลิกอนจากอุตสาหกรรมซีเมนต์และความเค็มต่อการเจริญเติบโต ผลผลิต และการเปลี่ยนแปลงทางสรีรวิทยาของข้าวพันธุ์หอมธรรมศาสตร์ - ชคตระการ สมชาย; ชุติมานุกูล พฤกษ์ (Thai Journal of Science and Technology, 2019)
Abstract The study on effect of silicon from cement industry and salinity applied into soil on growth and yield of Hom Thammasat rice variety was conducted in Factorial in CRD. The study factors were (1) level of silicon from cement industry consisting of 5 levels; 0, 200, 400, 600 and 800 kg/rai and (2) different levels of NaCl concentration consisting of 4 levels; 0, 25, 50 and 100 mmol/L. From the experiment, the results found that the increased level of Na concentration affected the plant growth (plant height, tiller number, root dry weight and shoot dry weight), the physiological response (photosynthetic rate, transpiration rate and stomatal conductance) and the productivity (filled seed, unfilled seed and seed yield per plant) to be decreased significantly. In addition, it was also found that the levels of silicon concentration showed no significant effect on the plant growth (plant height, tiller number, root dry weight and shoot dry weight). However, the level of silicon at 400 kg/rai increased the number of filled seed and decreased the number of unfilled seed significantly. Keywords: growth; Hom Thammasat rice variety; physiological change; salinity; silicon; yield